Archaeomaterials, innovation, and technological change - Erb-Satullo, Nathaniel L. (Elsevier, 2021)
The field of archaeomaterials research has enormous potential to shed light on past innovation processes. However, this potential has been only partially recognized outside its immediate practitioners, despite the fact that innovation and technology change are topics of enduring interest in archaeology and the broader social sciences. This review explores the relationship between archaeomaterials research and the interdisciplinary study of innovation, and maps out a path toward greater integration of materials analysis into these discussions. To foster this integration, this review has three aims. First, I sketch the theoretical landscape of approaches to the study of innovation in archaeology and neighboring disciplines. I trace how theoretical traditions like evolutionary archaeology have influenced archaeomaterials approaches to questions of technological change while also highlighting cases where work by archaeomaterials researchers anticipated trends in the anthropology of technology. Next, I distill a series of core concerns that crosscut these different theoretical perspectives. Finally, I describe examples where archaeomaterials research has deepened scholarly understanding of innovation processes and addressed these core questions. The future of archaeomaterials research lies in engagement with these broader discussions and effective communication of the contributions that materials analysis can make to building a comparative understanding of innovation processes.
Keywords: Diffusion; Pyrotechnology; Glass; Ceramics; Metallurgy; Transmission; Invention